Stem cell damage after chemotherapy- can we do better?. Issue 1 (March 2019) - Tang, Joy; Zhu, Nan; Rao, Sridhar; Carlson, Karen-Sue
Abstract: Therapy-related myeloid neoplasms are unintended and unwanted complications of cytotoxic chemotherapy and radiation. Unlike other environmental toxin-induced malignancies, exposure to the inciting agent is required to eradicate a primary and life-threatening cancer. In this review, we will focus on the biochemical mechanisms that lead to therapy-induced myeloid malignancy. This includes discussion of known mechanisms by which cytotoxic chemotherapy and radiation induce genetic mutations and promote evolution and expansion of malignant hematopoietic clones. Mechanisms by which the hematopoietic stem and progenitor microenvironment may be injured during the course of chemotherapy and radiation therapy will also be presented. While prevention strategies have not yet been brought into clinical testing or practice, there is active basic research relevant to prevention of t-MNs which is also included in our attempt to answer the question of whether we can do better to prevent stem cell injury after chemotherapy and radiation.